Intestinal Myiasis Due to Musca domestica: A Case Report (Bangladesh Journal of Medical Microbiology, 2012)
Puerperal sepsis is an important cause of maternal morbidity and mortality in developing countries. This study was Myiasis is the infestation of live human and vertebrate animals with dipterous larvae, which at least for a period, feed on the host's dead or living tissue, liquid body substances, or ingested food. Intestinal myiasis is usually an accidental phenomenon, which occurs due to the ingestion of eggs or larvae present in food. Usually the patient is asymptomatic and the larvae are excreted harmlessly in the faeces. In some case it may be associated with symptoms. The present paper describes such a case.DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10832